PERSPECTIVES ON CORRUPTION AND DEVELOPMENT: THE NIGERIAN VARIANTS - Abdullahi Shehu Gusau (European Scientific Journal, ESJ, 2013)
The raison det’re of any political entity is the pursuance of its very means of sustenance in its system; thus no political organisation ever exists without the cognizant presence of the basic tools for achieving some levels of development. Nigeria, just like any other political entity subsists in the international system with its basic tools for achieving the maximum level of political, economic and social development. Be it as it may sound, the achievement of any significant levels of development is under constant hindrances of a canker - worm that has eaten very deep into our social fabrics; an economic malaise that has deferred any level of a thematic econometric medication; a political decay that has proven over the years irresponsive to anti-corrosive political elements; i.e. corruption. Corruption have distorted Nigeria’s image both nationally and internationally. Nationally it has led to a total lack of political will on the part of our political entrepreneurs and lack of mass will on the part of the populace. Even the new democratic regimes could not meet the re-new hopes, vigor and aspirations that ushered it in, in 2009. It is on this backdrop that this paper titled:” Perspectives on corruption and Development: The Nigerian Variant”, intends to explore the impacts of corruption on development in Nigeria even as the country celebrates her centenary. This paper is divided into the following parts; (1). Introduction; (2). Theoretical Framework, (3). Corruption and Development: Conceptual issues, (4). Perspectives and Dimensions on corruption, (5). Impacts of corruption on Development: Political. Economic and Social, (6). Conclusion and Recommendations.